A novel social contact graph‐based routing strategy for workload and throughput fairness in delay tolerant networks. Issue 11 (22nd June 2016) - Le, Tuan; Kalantarian, Haik; Gerla, Mario
Abstract: Delay‐tolerant networks are sparse mobile ad hoc networks in which there is typically no complete path between the source and destination. Although many routing schemes for delay‐tolerant networks have been proposed, they do not address fairness issues in terms of the workload/traffic handled at each node and the share of throughput among different destination nodes. In this paper, we propose a socially aware routing strategy that optimizes both fairness and throughput. A relay node is selected based on the multi‐hop delivery probability and its queue length. The effect of queue length control is to divert traffic away from highly connected nodes and allows nodes to explore less‐congested paths to the destination. This helps balance the network loads, thus achieving workload fairness. Furthermore, to achieve throughput fairness, we sort arriving messages into different destination‐based queues. Messages are then scheduled following a two‐level forwarding strategy that optimizes throughput fairness using round‐robin and delivery ratio using priority scheduling. Extensive real‐trace‐driven simulation results show that our scheme outperforms existing algorithms in terms of the delivery ratio. Furthermore, our scheme achieves a high throughput fairness, while distributing the network loads more evenly, with the top 10% of network nodes handling only 22% of the forwardings. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Workload and throughput fairness are critical issues in delay tolerant networks that are largely ignored by many existing works. We found that the proposed queue length control strategy significantly improves workload fairness with the top 10% of network nodes handling only 22% of the forwardings. Furthermore, the proposed destination‐based multi‐queuing and the two‐level message scheduler can achieve a delivery rate of up to 8.2% higher than existing schemes, while maintaining a high throughput fairness with a Jain's value of 0.81.